The Prediction of Market Index Price - Abdelhedi, Mouna (Journal of Accounting, Business and Management (JABM), 2025)
This study undertakes the theory of stimulus organism response (SOR theory) to explain and predict investor emotion and investor behavior during the Covid-19 pandemic in France and Germany financial markets. In this paper, we apply the nonparametric volatility model, the vector autoregressive model, and the nonlinear autoregressive exogenous neural network model. Empirical results show a high level of jumps in investor emotion and investor behavior during the first wave of Covid-19. Moreover, we find the existence of emotional response to Covid-19, lockdown, and government support stimuli. Indeed, we find that Covid-19 stimuli enhance investor fear, while government support stimuli minimize the level of fear. Then, the investor emotion stimulates investor behavior, generating a behavioral response that confirms the SOR theory. However, we find that during the Covid-19 pandemic, market and bank stimuli present a lower effect on investor emotion compared with stimuli related to the Covid19 crisis. The Covid-19, lockdown, and government support stimuli efficiently predict investor emotion.